(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: It was always a challenge for hotel industry to find and retain skilled manpower and most of the hotels depend on in-house training programme to train and develop the employees as per their requirement. It is easy for hotels to retain staff if they are well-trained, they enjoy their work and are satisfied with workplace. COVID-19 pandemic presented one more challenge to hotel industry i.e., to embrace changes as per the expectations of market. Objectives: The main objectives of the study were to find out the impact of training towards employee satisfaction and change management. To establish the influence of employee satisfaction towards change management. Methodology: The factors shortlisted towards employee satisfaction were rewards, nature of work, supervision, benefits, work environment and co-workers. Factors identified for change management were strategic success, technological changes, effective systematic plan, communication, environment for change and change management. The research design for this paper was descriptive. The study was conducted for employee working in four major revenue producing operational departments. Total 16 hotels of city of Mumbai were approached for data collection. Due diligence was taken to collect data from different demographic profiles such as ownership pattern of hotels, department and experience of employees, their qualifications etc. Total 165 samples were collected. Data was corroborated using Cronbach’s alpha and hypotheses were validated using correlation and compare means one-way ANOVA tests with the help of SPSS software. Result: Main findings of study were that nature of work and supervision had moderate effect on work environment. Benefits, rewards and co-workers showed strong correlation. Co-workers and work environment strongly impacted employee satisfaction. Strategic success, environment for change and communication significantly affected change management. Conclusion: Training was found to have significant relationship with employee satisfaction and change management. Employee satisfaction had significant association with change management. However technological change and effective systematic plan (factors of change management) were not significantly associated.